An Exploring Obstacles and Teaching Strategies Used by Main Character in “Like Stars on Earth” Movie - Pureka, Mufida Nadira Yuni; Hasan, Hasan Khalawi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Speech act study is important for our daily because it gives a comprehension of what message is discovered in every utterance. Austin (1962) stated that in uttering a sentence, a speaker is generally involved in three levels of speech acts, they are locutionary act, illocutionary act, and perlocutionary act. This study focuses on analyzing illocutionary acts in “Like Stars on Earth” movie. This movie teaches teachers and parents in the world about how to understand the aptitudes and limitations of a child. This study used descriptive qualitative method within the framework of applied linguistics, i.e., discourse analysis. In collecting data, the writer was watching and observing the utterances of dialogues in a movie. The writer selected the data from the characters’ utterances which are related to the topic, especially about illocutionary speech acts to the data sheet. Then, categorizing the data into types of illocutionary speech acts. This study was taking the appropriate utterances and omitting inappropriate utterances. There were 359 utterances found in the utterances that uttered by the main character in this movie. Types of illocutionary acts were directive 195 times, representative 106 times, expressive 39 times, declarative 7 times, and commisive 12 times. From the total of the data above, the directives act served as the dominant form among the five types of illocutionary acts. It shows that the main character often gives expression to the hearer to do something.